Blood Pressure Variability as a predictor of maternal and neonatal outcomes in preeclampsia - Ryan Saktika Mulyana; Tjokorda Gede Astawa Pemayun; Ida Ayu Narayani; I Putu Gede Danika Adikarya; I Gusti Bagus Mulia Agung Pradnyaandara; I Gusti Ayu Cintya Paramyta (Universitas Airlangga, 2025)
HIGHLIGHTS Increased blood pressure variability (BPV) in preeclampsia is associated with a higher risk of maternal complications, such as prolonged hospitalization and eclampsia, as well as neonatal complications, including low birth weight and the need for NICU admission. Incorporating BPV monitoring into routine prenatal care may improve early detection of high-risk cases, allowing for timely interventions to reduce adverse maternal and neonatal outcomes. ABSTRACT Objective: Preeclampsia remains a major cause of maternal and perinatal morbidity and mortality worldwide. This study aimed to evaluate the impact of blood pressure variability (BPV) on maternal and neonatal outcomes in preeclamptic patients, emphasizing its potential role in clinical management. Materials and Methods: A retrospective cohort study was conducted on 40 preeclamptic patients treated at Prof. Dr. I.G.N.G Ngoerah Hospital, Denpasar, Bali, between January 2020 and December 2022. BPV was determined from serial systolic and diastolic blood pressure measurements during antenatal care. Maternal outcomes included length of hospitalization, preterm birth, premature rupture of membranes, eclampsia, postpartum hemorrhage, ICU admission, and composite adverse events. Neonatal outcomes included birth weight, Apgar scores, NICU admission, stillbirth, congenital anomalies, and neonatal death. Statistical analyses were performed using bivariate and multivariate logistic regression methods, with variables of p < 0.25 included in final models. Results: High BPV was significantly associated with increased maternal adverse events (adjusted OR 13.66; 95% CI 2.26–82.43; p = 0.004) and neonatal adverse outcomes (p = 0.011). Specifically, it correlated with low birth weight (p < 0.001), shorter birth length (p = 0.003), preterm birth (p = 0.003), and higher NICU admission rates (p = 0.005). No significant association was observed with fetal distress, intrauterine growth restriction, or neonatal death. The study achieved a statistical power of 86.7%. Conclusion: Increased BPV in preeclampsia is strongly linked to adverse maternal and neonatal outcomes. Routine BPV monitoring may serve as an important tool for early risk identification and improved obstetric management.